2015
DOI: 10.1093/nar/gkv960
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting control regions (ICRs) are marked by mono-allelic bivalent chromatin when transcriptionally inactive

Abstract: Parental allele-specific expression of imprinted genes is mediated by imprinting control regions (ICRs) that are constitutively marked by DNA methylation imprints on the maternal or paternal allele. Mono-allelic DNA methylation is strictly required for the process of imprinting and has to be faithfully maintained during the entire life-span. While the regulation of DNA methylation itself is well understood, the mechanisms whereby the opposite allele remains unmethylated are unclear. Here, we show that in the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 73 publications
3
43
0
Order By: Relevance
“…Besides the functional aberrations of H3K27me3 and H3K4me3 writers and erasers documented in many tumors (Suvà et al 2013;Dawson 2017), these control defects could also result from transcriptional changes in key tissuespecific transcription factors or cofactors. Studies in mouse ES cells and tissues showed that their transcriptionally inactive status is sufficient to promote the recruitment of the polycomb responsive complex PRC2 and H3K27me3 deposition at CGI/promoters (Mendenhall et al 2010;Klose et al 2013;Riising et al 2014;Jadhav et al 2016;Maupetit-Méhouas et al 2016). This suggests that the fate of bivalent chromatin domains upon development/ differentiation relies on the interplay between PRC2 and the availability of the ad hoc transcriptional machinery.…”
Section: Basis Of Transcriptional Alterations In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the functional aberrations of H3K27me3 and H3K4me3 writers and erasers documented in many tumors (Suvà et al 2013;Dawson 2017), these control defects could also result from transcriptional changes in key tissuespecific transcription factors or cofactors. Studies in mouse ES cells and tissues showed that their transcriptionally inactive status is sufficient to promote the recruitment of the polycomb responsive complex PRC2 and H3K27me3 deposition at CGI/promoters (Mendenhall et al 2010;Klose et al 2013;Riising et al 2014;Jadhav et al 2016;Maupetit-Méhouas et al 2016). This suggests that the fate of bivalent chromatin domains upon development/ differentiation relies on the interplay between PRC2 and the availability of the ad hoc transcriptional machinery.…”
Section: Basis Of Transcriptional Alterations In Cancermentioning
confidence: 99%
“…RT-qPCR assays were performed using a microfluidic-based approach as previously described (Maupetit-Méhouas et al 2016). First-strand cDNA was preamplified for 14 cycles with the pool of primers used for RT-qPCR and the TaqMan PreAmplification Master Mix (Life Technologies 4488593).…”
Section: Rt-qpcr Expression Analysesmentioning
confidence: 99%
“…Besides the functional aberrations of writers and erasers of the H3K27me3 and H3K4me3 marks documented in many tumors (16,17), these control defects could also result from transcriptional changes in key tissue-specific transcription factors or co-factors. Studies in mouse ES cells and tissues highlighted that their transcriptionally inactive status is sufficient to promote the recruitment of the polycomb responsive complex PRC2 and H3K27me3 deposition at CGI/promoters (44)(45)(46)(47)(48). This suggests that the fate of bivalent chromatin domains upon development/differentiation relies on the interplay between PRC2 and the availability of the ad hoc transcriptional machinery.…”
Section: Discussionmentioning
confidence: 99%
“…-Chromatin immuno-precipitation from glioma samples Anti-H3K9ac (Millipore 06-942), -H3K4me3 (Diagenode 03-050) and -H3K27me3 (Millipore 07-449) antibodies were used to assess the respective marks at selected genes by ChIP of native chromatin isolated from glioma samples and controls, as described in (48). Input and antibody-bound fractions were quantified by real-time PCR amplification with the SYBR Green mixture (Roche) using a LightCycler 480II (Roche) instrument.…”
Section: Chromatin Analysesmentioning
confidence: 99%
“…Imprinting patterns may vary between tissues 9 . Imprinted genes are mostly clustered and regulated by imprinting control regions (ICR), which are typically under DNA methylation control, though also H3K27me3 was recently demonstrated to be involved 10,11 . Imprinted genes play an important role in development and placental biology 12 .…”
mentioning
confidence: 99%